Introduction: STEM in US Popular Culture: Assessing Gender Discourse, Stereotypes and Mainstreaming - Álvarez Trigo, Laura; Tiburcio Moreno, Erika (REDEN. Revista Española de Estudios Norteamericanos, 2022)
-